Multicomponent, Solvent-Free Synthesis of 4-Substituted Aminopyrido[2,3-d]pyrimidines Derivatives - Fatima Belhadj; Zahira Kibou; Julio A. Seijas; Maria Pilar Vázquez-Tato; Noureddine Choukchou-Braham (Chemistry Proceedings)
4-substituted aminopyrido [2,3-d]pyrimidines derivatives 1a–f were synthesized via the multicomponent reaction of 2-aminopyridines, triethyl orthoformate, and diverse primary amines under solvent-free conditions. The present work creates a variety of fluorescent heterocyclic compounds in a short time and with good yields. The structures of all synthesized compounds were established by IR, 1H, and 13C NMR analysis.